Analisa Pengaruh Corporate Social Responsibility terhadap Produktivitas Karyawan pada Perusahaan Sektor NonKeuangan di Indonesia - Jennifer Eugene Chandra; Natasha Priscilla Yulianto; Saarce Elsye Hatane (Business Accounting Review, 2021)
The aim of this research is to investigate the effect of Corporate Social Responsibility on employee productivity measured by the ratio of the cost of employees to sales revenue. The hypothesis of this study was tested using a panel data regression model using Gretl application.This study thoroughly analyses 65 Indonesian non-banks and financial sectors listed on IDX that have ESG scores from 2015 to 2019. The empirical data for this paper is drawn from 325 observations by using CSR as the independent variable and the employee performance as the dependent variable. The results show that CSR is favourable for employee costs. The higher level of CSR disclosure, the lower the cost of employees used to produce sales revenue.